2015
DOI: 10.1080/09712119.2015.1091343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary propionic acid, sodium citrate, and phytase on growth performance, mineral digestibility, and tibia properties in broilers

Abstract: An experiment was conducted to determine the effects of supplementing a low available phosphorous (P) diet (0.14%) with phytase, propionic acid, and sodium citrate on performance, mineral metabolism, and tibia properties of broilers. A 2 × 2 × 2 factorial arrangement of treatments based a completely randomized design was used to evaluate the effects of phytase (0 and 300 units kg), propionic acid (0% and 0.2%), and sodium citrate (0% and 3%). The phytase improved feed conversion ratio (FCR) and increased feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…They stated that the reason for the increase in feed intake following the consumption of organic acids in broilers is related to the changes in the function of digestive enzymes, improvement of apparent digestibility, and improvement of intestinal microflora. The results of the present study showed that the use of organic acid increases feed intake, which is consistent with the results of Ghanaatparast-Rashti et al (2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They stated that the reason for the increase in feed intake following the consumption of organic acids in broilers is related to the changes in the function of digestive enzymes, improvement of apparent digestibility, and improvement of intestinal microflora. The results of the present study showed that the use of organic acid increases feed intake, which is consistent with the results of Ghanaatparast-Rashti et al (2015).…”
Section: Discussionsupporting
confidence: 92%
“…Organic acids can reduce the population of proteindegrading bacteria in the intestine and reduce the deamination of amino acids to eventually make more protein available to the animal for absorption, which in turn increases weight and improves performance. Ghanaatparast-Rashti et al (2015) in a study on different levels of propionic acid in broiler diets reported that the use of different levels of propionic acid (0.2, 0.4, and 0.8%) had a significant effect on their feed intake. They stated that the reason for the increase in feed intake following the consumption of organic acids in broilers is related to the changes in the function of digestive enzymes, improvement of apparent digestibility, and improvement of intestinal microflora.…”
Section: Discussionmentioning
confidence: 99%
“…The responses of poultry to the addition of PHY and CA in combination are quite inconsistent across the literature. Although positive effects of this association on performance, P digestibility, and tibia ash content have already been described in broilers (Ebrahimnezhad et al, ; Ghanaatparast‐Rashti et al, ), no significant differences between PHY alone and in combination with CA have also been observed in broilers (Afsharmanesh & Pourreza, ; Centeno et al, ), hens (Al‐Sharafat, Al‐Desiet, & Al‐Kouri, ; Nezhad et al, ; Nezhad, Sis, Gholshani, Saedi, & Aminvakili, ) and quails (Sacakli, Sehu, Ergun, Genc, & Selcuk, ). According to Brenes et al (), live performance and mineral retention are important measures in any mineral‐availability trial, but plasma and bone mineral concentrations are generally more sensitive than performance traits to assess the bioavailability of minerals.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, CA may also decrease the establishment of insoluble phytates in the gastrointestinal lumen by reducing digesta pH and promoting the protonation of phytic acid binding sites, which remain unavailable to form new bonds with dietary components (Emsley & Niazi, ). Despite these well‐known characteristics of CA and its potential to improve PHY effectiveness in breaking down phytic acid, poultry responses to the combined supplementation of PHY and CA have been quite inconsistent (Afsharmanesh & Pourreza, ; Centeno, Arija, Viveros, & Brenes, ; Ebrahimnezhad, Shivazad, Taherkhani, & Nazeradl, ; Ghanaatparast‐Rashti, Shariatmadari, Karimi‐Torshizi, & Mohiti‐Asli, ).…”
Section: Introductionmentioning
confidence: 99%
“…In broiler chickens, sodium citrate has been shown to have several beneficial effects, such as improving the growth rate of broiler chickens and the feed conversion ratio of broiler chickens, meaning they are able to convert feed into body weight more efficiently, as well as reducing the incidence of bone fractures and improving leg health. Sodium citrate can improve tenderness and juiciness of broiler meat, making it more desirable 1252 (2023) 012151 IOP Publishing doi:10.1088/1755-1315/1252/1/012151 2 for consumers [10,11,12]. Overall, sodium citrate can have several positive effects on broiler chickens, improving growth rate, feed conversion ratio, bone strength, and meat quality and there is some evidence to suggest that sodium citrate may have a positive effect on stress and immune response in broilers.…”
Section: Introductionmentioning
confidence: 99%